Enhancing Students’ Vocabulary Mastery in Arabic Language Learning Through Nearpod Media: The - Amir Supriatna Amir; Muhamad Farhan Zaqie Maulana (Assuthur: Jurnal Pendidikan Bahasa Arab, 2026)
This study aims to evaluate the effectiveness of using Nearpod media in enhancing students' vocabulary (mufradat) mastery in Arabic language learning. The research was motivated by the low level of vocabulary acquisition among eleventh-grade students at MAN 2 Kota Bandung, which is attributed to monotonous teaching methods and the limited use of interactive learning media that can engage students actively. A quantitative approach with a quasi-experimental design was employed, involving two groups: an experimental class that utilized Nearpod as a digital learning tool, and a control class that received conventional instruction without interactive media. Data were collected through pre-tests and post-tests to measure students’ vocabulary mastery before and after the treatment, and were analyzed using independent statistical tests and gain analysis. The results revealed a statistically significant difference between the two groups, with the experimental class showing a higher improvement in vocabulary mastery compared to the control class. These findings indicate that the use of Nearpod as an interactive learning medium is effective in supporting students’ vocabulary acquisition. Therefore, it is recommended that educators consider integrating interactive digital media into Arabic language instruction as an innovative strategy to enhance students’ learning outcomes.